Validation of hepatitis C virus RNA detection using capillary blood by finger prick (GenXpert system)—Hepatitis C fingerprick study. Issue 7 (13th March 2020) - Bielen, Rob; Koc, Özgür M.; Busschots, Dana; Verrando, Rita; Nevens, Frederik; Robaeys, Geert
Abstract: To achieve the ambitious goals of the WHO to eliminate hepatitis C virus (HCV) infection as a public health threat by 2030, innovative approaches are needed to improve the uptake for screening and treatment in people who inject drugs (PWID). Important barriers to care are difficult venous access and the two‐step approach in current point‐of‐care tests, using an HCV antibody screening test followed by a confirmatory HCV RNA test. In this study, we aimed to validate the new GenXpert instrument to diagnose HCV RNA by finger prick. This prospective study was conducted in a cohort of PWID in 6 alcohol/drug clinic sites and 1 outreach project in Belgium between January 2018 and March 2019. Plasma and capillary whole‐blood samples were collected by venepuncture and finger prick, respectively. Sensitivity and specificity of the GenXpert system were compared to the gold standard Artus HCV RNA kit. Of 153 participants enrolled, 147 (96.1%) had results of both the GenXpert system and Artus HCV RNA kit available. HCV RNA was detected in 35 of 147 (23.8%) by the Artus HCV RNA kit and in 36 of 147 (24.8%) by the GenXpert. Median quantitative HCV RNA viral load on finger prick was 28 700 IU/mL (IQR 4070‐65 875) vs 1 900 000IU/mL (IQR 416, 466‐2, 265, 510) on plasma. The GenXpert instrument had a sensitivity of 100% (95% CI 90%‐100%) and a specificity of 99.1% (95.1%‐99.9%). The overall diagnostic accuracy was 99.3% (96.3%‐99.9%). This study validates the excellent performance of the GenXpert instrument to assess HCV RNA in capillary whole blood by finger prick in a PWID cohort.